Development of smallholder dairying in Eastern Africa with particular reference to Kenya - Thorpe, W.R.; Muriuki, H.G.; Omore, Amos O.; Owango, M.O.; Staal, Steven J. (International Livestock Research Institute, 2000)
Large increases in demand for milk and dairy products projected for the next 25 years represent exciting market opportunities for smallholders in eastern Africa. With the exception of Kenya, traditional cattle production systems based on indigenous breeds dominate milk production in the region, yet they contribute relatively little to marketed production, mainly because of poor access to major urban markets. Kenya, which has over 85% of the dairy cattle population, dominates dairy production and marketing in the region. Its per capita milk availability is four to seven times higher than the other countries in the region. The widespread adoption of dairy cattle in Kenya was stimulated by several interacting factors: the conducive policy and institutional environments provided by successive Governments; the presence of significant dairy populations (owned by settler farmers); a sub-tropical geography suitable for dairy cattle; and, smallholder communities who kept cattle and who had milk as an important part of their diet.